The upstream player in Malaysia oil and gas industry: valuation of oil and gas companies / Mohd Zamrul Azuar Md Ali (Faculty of Business and Management, 2007)
This study was conducted to evaluate the upstream oil and gas companies in Malaysia. Since late 1990s, stock market analysts have focused strongly on shortterm accounting return measures, such as Return on Average Capital Employed (ROACE) and Reserve Replacement Ratio (RRR) for benchmarking and valuation of international oil and gas companies. Consequently, exaggerated capital discipline among oil and gas companies may have reduce their willingness to invest for future reserves and production growth. This is the reason why this study focuses on the market capitalization of oil and gas company. The aim of this study is to examine the relationship between market capitalization with ROACE and RRR of the oil companies. To determine the effect of ROACE and RRR to the market capitalization of oil company, this study using seven upstream oil and gas company in Malaysia. The time horizon is from the year 1992 to 2006 which is 15 years. The income statement and balance sheet are used to gather the ROACE and RRR information from of each company. There are two methods of data analysis used in this study; the time series regression and pooled regression analysis. The first method is done by analyzing each company separately. Researcher found out that there is no significant relationship between ROACE and RRR to the market capitalization of the oil company. Then the pooled regression is conducted in order to examine the relationship. By pooled the data from each company, researcher found out that RRR is significant contributor to the market capitalization of the oil company. The researcher findings do not support the general perception of ROACE as an important valuation metric in oil and gas industry.